2017
DOI: 10.1002/14651858.cd012009.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Amylase in drain fluid for the diagnosis of pancreatic leak in post-pancreatic resection

Abstract: Because of the paucity of data and methodological deficiencies in the studies, we are uncertain whether drain fluid amylase should be used as a method for testing for pancreatic leak in an unselected population after pancreatic resection; and we judge that the optimal cut-off of drain fluid amylase for making the diagnosis of pancreatic leak is also not clear. Further well-designed diagnostic test accuracy studies with pre-specified index test threshold of drain fluid amylase (at three times more on postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…When comparing CRP and plasma amylase in our cohort, the latter was significantly better in predicting complications. While drain fluid amylase is routinely used as a diagnostic marker for pancreas‐related complications after general pancreatic surgery, no relevant studies investigating its role in pancreas transplantation could be found 20 . Our results show that drain fluid amylase could be nearly as good as plasma amylase in predicting severe pancreas graft‐related complications, but plasma amylase showed more significant AUC values and was more precise in dividing patients between high and low morbidity groups, and for this reason, it was chosen as the primary variable.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing CRP and plasma amylase in our cohort, the latter was significantly better in predicting complications. While drain fluid amylase is routinely used as a diagnostic marker for pancreas‐related complications after general pancreatic surgery, no relevant studies investigating its role in pancreas transplantation could be found 20 . Our results show that drain fluid amylase could be nearly as good as plasma amylase in predicting severe pancreas graft‐related complications, but plasma amylase showed more significant AUC values and was more precise in dividing patients between high and low morbidity groups, and for this reason, it was chosen as the primary variable.…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 Cochrane review reported great variability in reporting of POPF, in terms of operative days and different cut-off values 15. Some studies identified a patient with pancreatic fistula after radiological confirmation, before using ISGPF classification to stratify POPF.…”
Section: Discussionmentioning
confidence: 99%
“…[38] Throughout the abdominal cavity, drainage uid from pancreatic cancer patients has only been used as a diagnostic indicator of pancreatic leaks or ascites, unlike wound uid from breast cancer surgery. [39,40] Various cancers, including pancreatic cancer, are known to protect malignant cells and accumulate uid (malignant effusion) through the secretion of cytokines, growth factors, or peptides. [41] Several studies have investigated the tumour microenvironment through PF analysis for other cancer types, but little research has been conducted on PF in pancreatic cancer to date.…”
Section: Discussionmentioning
confidence: 99%